A CASE STUDY ON ANALYSING THE POTENTIAL OF SAARC FOR ENHANCING REGIONAL COOPERATION ON CLIMATE CHANGE - Nawale (Kadam), Pramodini Balasaheb (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The South Asian Association for Regional Cooperation (SAARC) has immense potential to drive regional collaboration in addressing climate change challenges. This study explores the role of SAARC as a platform for fostering cooperation among South Asian nations on climate change mitigation, adaptation, and sustainable development. With diverse ecosystems, high vulnerability, and shared socio-economic challenges, the region requires coordinated efforts to tackle climate impacts. The research examines the initiatives undertaken by SAARC, evaluates their effectiveness, and identifies opportunities for improvement. This case study underscores the need for policy harmonization, resource sharing, and capacity building to unlock SAARC’s potential as a regional climate action leader.